Sayyidah Nafisah, Seorang Sufi Ulama Perempuan - Anisah, Rafiqatul; Kibtiyah, Asriana (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. Women and gender studies continue to find momentum, but female clerics are almost never studied. This is early evidence of the assumption that women are not significant in the clergy or even the scientific world in general.Aim. This paper aims to show that female clerics must be recognized for their clergy and knowledge, rights, roles and existence, both in the scientific context and in the life of the nation and state.Methods. This paper designed with the literature study method.Results. Sayyidah Nafisah is the great-grandson of the Prophet Muhammad. She is an example that the existence of female clerics has significance in the context of clergy and the scientific world in general. It is time for society to recognize the existence of female clerics who have the rights and obligations to realize the ideals of the nation and state by developing a moderate, tolerant perspective, respecting diversity.